CONSTRAINTS IN THE USE OF INFORMATION AND COMMUNICATION TECHNOLOGY (ICT) BY SCIENCE TEACHERS IN FOSTERING NATIONAL UNITY IN ENUGU STATE - Ugwoke, Dr. P.U (Journal of Continuing and Development Education, 2023)
The Study investigated the constraints in the use of information and communication Technology by science teachers in fostering national unity in Enugu State. Two research questions guided the study. The Design of the study is descriptive Survey Research design which is much appropriate in the study because the researcher is seeking the respondents’ opinions. Enugu State was the area of the study. The population of the study is too science teacher drawn from the three local governments. The researcher using simple random sampling technique sampled Nsukka education Zone. Education is made of Nsukka local government Igbo Etiti and uzor Uwani local government. The instrument for data collection was questionnaires developed by the researcher which was subjected to validation by three experts two from Computer unit and one from measurements and evaluation unit, University of Nigeria Nsukka. The Reliability of the instruments were tested using Kuder Richardson K-r20 approach which yielded a reliability index of 0.98 which means that the instruments are Reliable. The research questions were answered using mean and standard deviation. Based on the findings it evident that science teachers do not use ICT in teaching sciences and to achieve National Unity using ICT becomes difficult. Hence Conclusion were drawn and recommended were made